Expanding the Repertoire of Carbapenem-Hydrolyzing Metallo-ß-Lactamases by Functional Metagenomic Analysis of Soil Microbiota - Gudeta, Dereje D.; Bortolaia, Valeria; Pollini, Simona; Docquier, Jean-Denis; Rossolini, Gian M.; Amos, Gregory C. A.; Wellington, Elizabeth M. H.; Guardabassi, Luca (Frontiers in Microbiology, 2016)
Carbapenemases are bacterial enzymes that hydrolyze carbapenems, a group of last-resort β-lactam antibiotics used for treatment of severe bacterial infections. They belong to three β-lactamase classes based amino acid sequence (A, B and D). The aim of this study was to elucidate occurrence, diversity and functionality of carbapenemase-encoding genes in soil microbiota by functional metagenomics. Ten plasmid libraries were generated by cloning metagenomic DNA from agricultural (n=6) and grassland (n=4) soil into Escherichia coli. The libraries were cultured on amoxicillin-containing agar and up to 100 colonies per library were screened for carbapenemase production by CarbaNP test. Presumptive carbapenemases were characterized with regard to DNA sequence, minimum inhibitory concentration (MIC) of β-lactams, and imipenem hydrolysis. Nine distinct class B carbapenemases, also known as metallo-beta-lactamases (MBLs), were identified in six soil samples, including two subclass B1 (GRD23-1 and SPN79-1) and seven subclass B3 (CRD3-1, PEDO-1, GRD33-1, ESP-2, ALG6-1, ALG11-1, and DHT2-1). Except PEDO-1 and ESP-2, these enzymes were distantly related to any previously described MBLs (33 to 59% identity). RAIphy analysis indicated that six enzymes (CRD3-1, GRD23-1, DHT2-1, SPN79-1, ALG6-1 and ALG11-1) originated from Proteobacteria, two (PEDO-1 and ESP-2) from Bacteroidetes and one (GRD33-1) from Gemmatimonadetes. All MBLs detected in soil microbiota were functional when expressed in E. coli, resulting in detectable imipenem-hydrolyzing activity and significantly increased MICs of clinically relevant ß-lactams. Interestingly, the MBLs yielded by functional metagenomics generally differed from those detected in the same soil samples by antibiotic selective culture, showing that the two approaches targeted different subpopulations in soil microbiota.